Penguasaan Konsep dan Motivasi Belajar Siswa Kelas V melalui Pembelajaran Berbasis Proyek Menggunakan Aplikasi WhatsApp (Penelitian Deskriptif Kualitatif pada Siswa Kelas V Di SD Negeri Bunter 1 Kecamatan Cimanggung) - Nuraeni, Desi; Sudin, Ali; Sujana, Atep (Jurnal Pena Ilmiah, 2021)
This study aims to determine the effect of project-based learning on concept mastery and students' learning motivation related to the water cycle theme. The method used is qualitative research with a descriptive approach. The subjects in the study were the fifth-grade elementary school students in Sumedang District, totaling 20 people. The instrument used consisted of a scale of observations, tests, and questionnaires given before and after project-based learning. The results showed that there was an increase in students' mastery of concepts after learning, from the average value of students' science affective increased 4.3 to 5. There was also the effect of project-based learning on student learning outcomes of student learning motivation because in the results of the questionnaire that obtained the interest 85% of students answered agree on it can be said that the learning interest of fifth-grade students is very good in the implementation of science learning.